REALITAS DAN TANTANGAN INOVASI PENYELENGGARAAN PEMERINTAHAN (Perspektif Reformasi Administrasi di Indonesia) - G. Suharto, Didik (Jurnal Desentralisasi, 2012)
The government innovation proceeds in line with the administrative reformation movement. The innovative government frequently finds the momentum in thegovernment in which the administration has experienced reformation. In Indonesia, the administrative (bureaucracy) reformation discourse is articulated widely along with the total reformation demand in 1997-1998. However after more than one decade, the implementation of such the administrative reformation had not been as expected. The administrative reformation experiences stagnation, even in some case, it shows paradoxical situation. Congruent to the administrative reformation development, the governmental innovation development (central and local) has not reached the maximal result. The government innovation still tends to be sporadic, sectoral and regional. The effectiveness and sustainability of governmental innovation currently proceed are still questioned. The improvement in bureaucracy system and human resource management is considered as important to cope with the challenge in institutionalizing the governmental innovation proven good.